Keynote Address - Anyanwu, Professor John C. (My University, 2012)
From 1995 to 2008, Africa’s average economic growth was 5% per annum. In 2008 GDP growth in Africa was 5.5% against 6.5% in 2007, representing the fifth consecutive year when growth exceeded 5.5%. This has largely been attributed generally as the dividend of the reforms embarked upon by most African countries during the period.
Keywords: keynote address